The role of the Lestari Farmers Group Cooperative in improving the economic welfare of the Taratak Jarang Community in Solok Regency - Sari, Fitri mayang; Akmal, Artha Dini (Priviet Social Sciences Journal, 2025)
The Lestari Cooperative Farmers Group is a solution to the challenges faced by the community in Nagari Taratak Jarang, Solok Regency, particularly the difficulty in accessing business capital owing to limited banking services. Banking institutions often implement complex procedures and requirements that are difficult for individuals without a collateral or adequate credit history to meet. This study aimed to evaluate the contribution of cooperatives and obstacles experienced by farmer groups in their efforts to improve the economic welfare of the Taratak Jarang community. The research method applied is descriptive qualitative, with informants selected through purposive sampling, including the Cooperative Chair, Secretary, Treasurer, and cooperative beneficiaries. Data sources include primary data obtained from interviews and documentation and secondary data from the Central Statistics Agency (BPS), literature, reports, journals, and other sources. Data analysis was conducted based on the Miles and Huberman framework, which involves data reduction, data presentation, and drawing conclusions. The research findings indicate that the Lestari Cooperative Farmers Group in Taratak Jarang makes a substantial contribution to the economic welfare of its members through savings, loan services, and capital support, although administrative processes and financial recording are still carried out manually. Guidance is provided through deliberations and regular meetings, but the lack of formal training in cooperative and business management hinders the improvement of skills among both the management and members. Member participation is generally good but inconsistent due to economic factors, workload in the field, and a lack of understanding of the cooperative's benefits. Human resources, finances, and facilities have been utilized fairly well, but the potential has not been fully realized because of managerial limitations and slow technology adoption. The minimal use of digital devices for bookkeeping and communication is a major obstacle to work efficiency and effectiveness.